2008
DOI: 10.3344/kjp.2008.21.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Zoster in Healthy Child: A case report

Abstract: Herpes zoster in childhood is uncommon, but it is more common in association with immunosuppression. Maternal varicella infection during pregnancy and varicella occurring in the newborn represent risk for childhood herpes zoster. However, some controversies persist on risk factors, diagnosis, and the natural history of childhood disease. We report a 10-year-old healthy boy with shingles and review the risk factors, prognosis, and treatment of pediatric zoster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Due to the biological differences between the genders, the virus is more likely to reactivate in the female body than in the male body. The study also cited the higher exposure rate of females to children with chickenpox as one of the reasons behind the higher incidence rate [ 15 16 17 18 ]. The present study also found a higher proportion of female patients with shingles (M:F = 1:1.42).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the biological differences between the genders, the virus is more likely to reactivate in the female body than in the male body. The study also cited the higher exposure rate of females to children with chickenpox as one of the reasons behind the higher incidence rate [ 15 16 17 18 ]. The present study also found a higher proportion of female patients with shingles (M:F = 1:1.42).…”
Section: Discussionmentioning
confidence: 99%